Model of Implementation of Juvenile Criminal System to the Criminal Offender (Educative Perspective on Institute for Special Development Children LPKA Kutoarjo, Central Java, Indonesia) - Arifin, Mokhammad Dony (JILS (Journal of Indonesian Legal Studies), 2018)
The Kutoarjo Class I Special Guidance Institute Purworejo Regency, Central Java, the author chose as a research locus, because he wanted to see the extent of Article 1 paragraph 2 of Law Number 12 of 1995 implemented. The formulation of the problem in this study as follow: (1) how is the implementation of juvenile crime on criminal offenders in an educative perspective at the Kutoarjo Class I Special Guidance Institute Purworejo District, Central Java? (2) What is the model of the implementation of child crime on criminal offenders in an educative perspective at the Kutoarjo Class I Special Guidance Institute Purworejo District, Central Java? This study aims to: (1) Describe the implementation of juvenile crime on criminal offenders in an educative perspective at the Kutoarjo Class I Special Training Institute Purworejo District, Central Java. (2) Finding a model of the implementation of juvenile crime on criminal offenders in an educative perspective at the Kutoarjo Class I Special Guidance Institution in Purworejo District, Central Java. The results of research on the implementation of juvenile crime on criminal offenders in an educative perspective at the Kutoarjo First Class Special Guidance Institution in Purworejo Regency, Central Java have not been fully and consistently implemented. This is evidenced by the inconsistencies in the schedule for the existing children facing the law (Anak Berhadapan dengan Hukum, ABH). It is also proven by the lack of competent educators in their respective fields. With the formation that is still theoretical, it can be guaranteed that the ABH will not be able to become a new person who is confident later, because it will be continuously shadowed about jugde as a prisoner. This mindset that must be changed from now on, with various kinds of learning using the Islamic boarding school model that is taught and instilled since in prison, will bring positive impact on ABH along with its good future.